Analysis of Young Consumer Loyalty Strategies in the Culinary Business through the SWOT–TOWS Approach and Interpretive Structural Modeling (ISM) - Siti Zuliani; M. Gibran Rifka Pramudia; Ratih Amelia; Hujjatullah Fazlurrahman; Dana Azizah Rahmat (Petra International Journal of Business Studies, 2026)
In the digital era, building Generation Z customer loyalty has become a major challenge for culinary businesses due to rapidly changing consumer behavior and the strong influence of social media. This study aims to formulate priority strategies for strengthening young consumer loyalty through an integrated SWOT–TOWS and Interpretive Structural Modeling (ISM) approach. A case study was conducted at Mie ABC using digital audits, field observations, and interviews with business stakeholders and consumers aged 17–25 years. The SWOT–TOWS analysis generated sixteen strategic alternatives, which were further analyzed using ISM and MICMAC to identify hierarchical relationships and strategic priorities. The results indicate that customer feedback utilization, TikTok virality, recipe consistency, and product quality are key drivers in building loyalty. Furthermore, all strategic elements demonstrate high interdependence, suggesting that loyalty is shaped through the synergy of digital marketing, operational excellence, customer experience, and community engagement. These findings provide valuable insights for developing long-term loyalty strategies among young consumers. This study contributes an integrated SWOT–ISM framework and provides practical guidance for culinary SMEs seeking sustainable customer loyalty in a digital marketplace.